Can the Scapular Dyskinesis Test be Associated with Throwing Related Injuries During the Course of Collegiate Baseball Seasons? - Masaaki Tsuruike; Yohei Mukaihara; Todd S. Ellenbecker (North American Sports Medicine Institute, 2022)
# Background A pattern of scapular dyskinesis on the dominant side has been demonstrated to be associated with a decrease in throwing arm conditions identified by a self-report outcome assessment in collegiate baseball pitchers during the course of a single season. However, it is unclear if symptomatic shoulders in baseball pitchers may be associated with the presence of scapular dyskinesis. # Purpose To study the relationship between the presence of scapular dyskinesis and throwing-related injury in collegiate baseball pitchers during each respective course of up to four subsequent seasons. # Methods A single Division 1 National Collegiate Athletic Association team participated in this study over a four-year-period. The scapular dyskinesis test was implemented during the preseason for baseball pitchers. Players were followed throughout each respective season to track the incidence of throwing-related upper extremity injuries. # Results A total of 36 collegiate baseball pitchers (height: 185.3 ± 5.6 cm, weight: 88.8 ± 7.8 kg, age: 20.0 ± 1.5 years) consisting of 57 pitcher seasons were followed in this study, in which 18 pitchers remained with the team for more than one year. Twenty-seven of the 57 pitchers were classified as having scapular dyskinesis demonstrated at around 90° of shoulder flexion on the throwing side. Five injuries (13.2% of a total of 38 injuries) were diagnosed as throwing-related shoulder injuries during the course of the intercollegiate baseball seasons. Four of the five throwing-related shoulder injuries occurred in pitchers who had scapular dyskinesis on their dominant side. Consequently, the odds ratio was 5.04 for the collegiate pitchers with scapular dyskinesis on the throwing arm side associated with a throwing-related shoulder injury compared to those with no scapular dyskinesis (p = 0.16). No relationship was identified between scapular dyskinesis on the throwing arm side and throwing-related elbow injury. Eighty-one percent of the scapular dyskinesis test results were not changed on the throwing side from the previous to the following year for those 18 pitchers who were followed for more than one season, whereas 42.9% of the results remained unchanged on the non-throwing side. # Conclusion The results suggest that collegiate baseball pitchers with dominant arm scapular dyskinesis likely are at increased risk of throwing-related shoulder injury. # Level of evidence Level 2, Prospective Cohort Study